Meta-analysis of the Effect of Excess Waist Circumference on Hypertension Incidence in Adolescents - Ulul Azmi Zuhaira; Viola Fathia Irwan (Masters Program in Public Health, 2022)
Background: Hypertension is a condition characterized by blood pressure measurements showing a systolic pressure of >130 mmHg and a diastolic pressure of >80 mmHg. There are so many cases of hypertension in adolescents that begin with being overweight or obese. One way to determine a person's level of obesity is by measuring the waist-to-hip ratio. This study was aimed to analyze the effect of excess waist circumference on the incidence of hypertension in adolescents. Subjects and Method: This study is a meta-analysis study with the following PICO, population: adolescents. Intervention: excess waist circumference. Comparison: normal waist circumference. Outcome: hypertension. This study uses PRISMA flowchart guidelines. The article search process was carried out between 2011-2021 using online databases, namely PubMed, Google Scholar, and Science Direct. Based on the database, there were 9 articles that met the inclusion criteria. The analysis was carried out using RevMan 5.3 software. Results: There are 9 cross-sectional studies originating from 2 continents, namely America and Asia. Based on the data showed that adolescents with excess waist circumference increased the risk of hypertension 1.59 times compared to adolescents with normal waist circumference (aOR= 1.59; 95% CI= 1.00 to 2.52; p= 0.050). Conclusion: Excess waist circumference increases the risk of hypertension in adolescents. Keywords: hypertension, waist circumference, teens Correspondence: Ulul Azmi Zuhaira. Politeknik Kesehatan Kemenkes Malang. Jl. Besar Ijen No. 77 C, Oro-oro Dowo, Kec. Klojen, Kota Malang, Jawa Timur. Email: ululazmizuhaira@gmail.com. Mobile: +62822-4501-2258.